Novos marcadores de doença coronária aguda: Síndrome coronário agudo - Filipa Manuela Gomes de Abreu Martins (2019)
The diagnosis of AMI is one of the areas that has been studied the most to decrease morbidity and mortality of the disease, so there has been a growing interest in the search for new markers of Acute Coronary Syndrome (ACS). The aim of this work is to review the biological markers of atheromatous plaque rupture/erosion and new markers of myocardial necrosis. There is increasing evidence of the benefit of new plaque instability biomarkers, some of which are promising, such as galectin-3, hyaluronic acid, matrix metalloproteinases and myeloperoxidase. The list of microRNAs and their interest in early diagnosis of ACS has increased, as has a search for a set of genes that indicate an increased risk of ACS. Most are still at an early stage of knowledge, requiring further studies to indicate their role in clinical practice, and whether they bring some benefit when compared to current diagnostic methods. The interest of myocardial necrosis markers seems to have been exhausted in the quantification of troponin. However, other markers have appeared in this context such as copeptin, galectin-1 and cMyc, which are waiting for further studies to place them on the path of early markers of ACS.